Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Welcoming Ceremony to the Delegates of Emerging Leaders' Dialogues Asia 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
First and foremost, it gives me great pleasure to welcome all the 10 delegates of ELDA 2016 to the Pekan Campus of Universiti Malaysia Pahang this afternoon in conjunction with your study tour sponsored by the Commonwealth Study Conference Association of Malaysia (COSCAM) and Association of Emerging Leaders’ Dialogue (AELD) .